Analisis Pendapatan dan Pertumbuhan Perekonomian Kota Bogor pada Tahun 2016-2020 - Hery Haryanto; Yuni Nuraeni; Martasya Martasya; M Mardin Zen (Owner : Riset dan Jurnal Akuntansi, 2022)
Income earned by an area in a certain time. The existence of income earned by an area at a certain time has an impact on economic conditions in the area. Bogor City is one of the regions in West Java Province with a fairly good economic movement in 2016-2020, it can be seen in terms of Regional Original Income (PAD) which decreased and increased from 2016-2020. This study will analyze the income received by the city of Bogor in 2016-2020, and will increase economic growth in the city. This study uses a quantitative method, where various data are taken from previous research and using data released by the Bogor City government in 2016-2020. This study found that Bogor City's income was quite good because it was able to increase PAD in 2019 and 2020. This result had an impact on Bogor City's economic growth which also increased. This study concludes that income and good economic development will have a good impact on a certain area for both infrastructure and non-infrastructure development.